The corsairs' longest voyage : the Turkish raid in Iceland 1627 - Þorsteinn Helgason (History of warfare, 2018)
During the summer of 1627, corsairs from Algiers and Salé, Morocco, undertook the long voyage to Iceland where they raided the eastern and southern regions of the country, resulting in the deaths of around thirty people, and capturing about 400 further individuals who were sold on the slave markets. Around 10% of the captives were ransomed the next twenty years, mostly through the efforts of the Danish monarchy. In this volume, the history of these extraordinary events and their long-lasting memory are traced and analysed from the viewpoints of maritime warfare, cultural encounters and existential options, based on extensive use of various sources from several languages.